(untitled) (MSW Management Journal, 2026)
Background: Titanium and its alloys are widely used in biomedical implants due to their excellent mechanical strength, corrosion resistance,and biocompatibility. Surface characteristics play a crucial role in osseointegration and overall implant success. Recent advances in laser surfacemodification allow precise control over implant topography, potentially enhancing biological performance.Aim: To evaluate the influence of laser-microtextured surface patterns (grooves, dimples, and random structures) on the physicochemical andbiological properties of titanium plates.Materials and Methods: This in-vitro experimental study included sixteen commercially pure Grade 4 titanium plates divided into four groups(n = 4): sandblasted control, laser-grooved (G1), laser-dimpled (G2), and laser-random (G3). Surface modification was performed using a pulsedNd:YAG laser. Surface roughness was assessed using atomic force microscopy (AFM). Wettability was evaluated by contact angle measurement.Cytocompatibility was analyzed using MG-63 osteoblast-like cells via MTT assay and Live/Dead staining. Hemocompatibility was assessedusing a haemolysis assay, and antimicrobial activity was evaluated against Porphyromonas gingivalis. Statistical analysis was performed usingTukey HSD post hoc tests.Results: The grooved surface (G1) exhibited the highest surface roughness (Sa: 300.49 ± 4.14 nm), while dimpled (G2) and random (G3) surfacesshowed lower roughness values. Wettability analysis revealed the lowest contact angle in G1 and highest in G2. All groups demonstrated highcell viability (>90%) with no significant differences (p > 0.05). Hemolysis values were below 5% in all groups, indicating acceptablehemocompatibility, though G1 showed comparatively higher values. Laser-modified surfaces, particularly the random pattern (G3), demonstratedreduced bacterial adhesion.Conclusion: Laser microtexturing significantly influences surface characteristics and biological responses of titanium implants in a patterndependent manner. Among the tested designs, the random microstructured surface exhibited a favorable balance of wettability,hemocompatibility, and antimicrobial properties, making it a promising approach for enhancing implant performance.